Photocatalytic degradation of methylene blue dye on reticulated vitreous carbon decorated with electrophoretically deposited TiO2 nanotubes - Zaidi, Syed Z. J.; Harito, Christian; Bavykin, Dmitry; Martins, Alysson S. [UNESP]; Yuliarto, Brian; Walsh, Frank C.; Leon, Carlos Ponce de (Elsevier B.V., 2020)
Titanate nanotubes (TiNT) were deposited over the surface of 100 pores per inch (ppi) reticulated vitreous carbon (RVC) by anodic electrophoresis at a cell voltage of 15 V, in an undivided cell, from an ethanol/water suspension containing TiNT coated with tetrabutylammonium hydroxide (TBAOH) surfactant. Scanning electron microscopy showed the open cell porous structure of TiNT/RVC coated by a uniform ca. 30 mu m thick layer of TiNT. Calcination at 450 degrees C for 2 h in air improved the photocatalytic properties. The material was used as photocatalyst for the decolourisation of methylene blue (MB) dye. The 98% volumetric porosity of the RVC substrate provided good reactant access and large surface area for deposition of TiNT. The calcined TiNT/RVC substrate achieved a 91% dye degradation after 20 min, which was higher than uncoated, acid treated RVC and non-calcined TiNT/RVC substrate. The MB decolourisation improved at an increased thickness of 3D TiNT/RVC catalyst although the improvement was limited to 4 mm on 100 ppi RVC due to limited UV penetration.
Keywords: Catalytic processes; Composites; Glassy carbon; Ion assisted deposition; Nanotubes